Production of methane from poultry manure - Wi Ven, Lai (2012)
Poultry industry is a fast growth industry globally in line with high demand in the Halal meat at Islamic countries especially in Malaysia.Increasing number in broiler production creates a lot of environment issues.The recent stunning issue that attracts the attention of the public is about 400 tons of unsolved chicken dung in Selangor that arisen air,water and soil pollution.Fermentation process is the ideal way to solve the problem with win-win situation. Besides producing clean energy with low carbon emission, the sludge obtained after fermentation process is very suitable for landfill as fertilizer.There are 3 same size carboys with 25 liter volume fabricated as fermenters.They are fed-batch with inoculums fermenter,fed-batch without inoculums fermenter and lastly a batch fermenter.After adding 17 liters of sample with 10% TS w/v for each fermenter,the fermenters are purged with pure nitrogen gas for 30 minutes and later placed inside a fabricated polytank with heating system as water bath to maintain the temperature within 55 degree Celsius which is thermophile anaerobic condition.An additional of 1.7 liters of sewage sludge (inoculums) is added to the inoculums fermenter .The quantity of gas produced is checked and recorded every days by gas displacement system and the gas composition is checked gas analyzer once a week.For fed-batch fermenters, one sixth of 17 liters is withdrawn once a week,at the same time,same amount of fresh diluted sample is pumped in by using peristaltic pump.By comparing batch with and without inoculums fermentation, applications of inoculums in batch fermentation shorten the lag phase and leads to a shorter fermentation cycle in batch system.By comparing the same thermophile system between batch and fed-batch fermentation process,both of the process give similar result in term of biogas production and methane gas composition during lag phase.However,the biogas production for thermophile fed-batch system keep maintaining at log phase whereas thermophile batch system encounter its’ stationary phase at the day 14th and death phase at day 40th.In short, application of inoculums in fermentation accelerates the biogas production and fed-batch fermentation is suitable for commercial purpose as the biogas produced is continuous with low down time.